Erythrocytic alpha-synuclein as potential biomarker for the differentiation between essential tremor and Parkinson’s disease - Yu, Zhenwei; Liu, Genliang; Zheng, Yuanchu; Huang, Guoshi; Feng, Tao (Frontiers in Neurology, 2023)
The differentiation between essential tremor (ET) and Parkinson's disease (PD) can be difficult because of the symptom overlaps. Erythrocytes are the major source of peripheral α -synuclein ( α -syn), which is the most studied pathological molecular of PD. We have reported that erythrocytic α-syn levels in PD patients are significantly increased compared to those in healthy controls (HCs).However, little is known about the levels of erythrocytic α-syn species in ET patients.This study includes 15 patients with ET, 64 patients with PD, and 49 age and sex matched HCs. A well-established electrochemiluminescence assay was used to measure the erythrocytic total and aggregated α-syn levels. The receiver operating characteristic (ROC) curve analysis was applied to evaluate the diagnostic values of erythrocytic α -syn for ET diagnosis and differentiation. The correlations of erythrocytic α-syn levels with disease durations were tested using Spearman's Rank Correlation analysis.We found that both erythrocytic total and aggregated α -syn concentrations are significantly increased in PD and ET patients compared to those in HCs.Erythrocytic total α -syn levels are significantly higher in ET patients than those in PD group. Furthermore, the ratios of erythrocytic aggregated to total α-syn levels in ET patients are significantly decreased than those in PD and HC subjects. We also found a significant association of erythrocytic aggregated α -syn levels with the disease duration of ET patients.Our findings suggest new insight into the changes of erythrocytic total and aggregated α-syn levels as potential biomarkers for ET patients.